War of the chatbots: Bard, Bing Chat, ChatGPT, Ernie and beyond. The new AI gold rush and its impact on higher education (Journal of Applied Learning and Teaching, 2023)
Developments in the chatbot space have been accelerating at breakneck speed since late November 2022. Every day, there appears to be a plethora of news. A war of competitor chatbots is raging amidst an AI arms race and gold rush. These rapid developments impact higher education, as millions of students and academics have started using bots like ChatGPT, Bing Chat, Bard, Ernie and others for a large variety of purposes. In this article, we select some of the most promising chatbots in the English and Chinese-language spaces and provide their corporate backgrounds and brief histories. Following an up-to-date review of the Chinese and English-language academic literature, we describe our comparative method and systematically compare selected chatbots across a multi-disciplinary test relevant to higher education. The results of our test show that there are currently no A-students and no B-students in this bot cohort, despite all publicised and sensationalist claims to the contrary. The much-vaunted AI is not yet that intelligent, it would appear. GPT-4 and its predecessor did best, whilst Bing Chat and Bard were akin to at-risk students with F-grade averages. We conclude our article with four types of recommendations for key stakeholders in higher education: (1) faculty in terms of assessment and (2) teaching & learning, (3) students and (4) higher education institutions.